The killer's game [videorecording (Blu-Ray + DVD)] - Ravich, Rand; Coyne, James (Screenwriter); Bonansinga, Jay R.; Bautista, David, 1969-; Boutella, Sofia, 1982-; Crews, Terry, 1968-; Adkins, Scott, 1976-; Klementieff, Pom; Kingsley, Ben, 1943-; Zaror, Marko, 1978-; Cork, Lucy; Bonansinga, Jay R. (Lionsgate, 2024)
In the new action-comedy when top hitman Joe Flood is diagnosed with a terminal illness, he decides to take matters into his own hands by taking a hit on himself. But when the very hitmen he hired also target his ex-girlfriend, he must fend off an army of assassin colleagues and win back the love of his life before it's too late.